1999
DOI: 10.1210/endo.140.12.7208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP-38)/Vasoactive Intestinal Polypeptide Receptors in Pancreatic β-Cells and Effects of PACAP-38 on Components of the Insulin Secretory System1

Abstract: It has been previously demonstrated that pituitary adenylate cyclase-activating polypeptide (PACAP) regulates insulin secretion. PACAP exerts its biological action by binding to at least three different receptor subtypes coupled to different signal transduction mechanisms. The signaling pathways underlying the insulinotropic effect of PACAP involve mainly the activation of adenylate cyclase to form cAMP, which directly and indirectly, through increased intracellular Ca2+, stimulates insulin exocytosis. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 48 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…In the current study, we show that PACAP interacts only with PAC 1 R to stimulate the MEK/ ERK1/2 cascade. In pancreatic ␤-cells, PAC 1 R is highly expressed, and binding studies indicate that PAC 1 R prevails over VPACR (41). The functional role of PAC 1 R has been confirmed in PAC 1 R-deficient mice, and we have shown that PAC 1 Rs are required for an optimal glucose-stimulated insulin secretion (40).…”
Section: Discussionsupporting
confidence: 57%
“…In the current study, we show that PACAP interacts only with PAC 1 R to stimulate the MEK/ ERK1/2 cascade. In pancreatic ␤-cells, PAC 1 R is highly expressed, and binding studies indicate that PAC 1 R prevails over VPACR (41). The functional role of PAC 1 R has been confirmed in PAC 1 R-deficient mice, and we have shown that PAC 1 Rs are required for an optimal glucose-stimulated insulin secretion (40).…”
Section: Discussionsupporting
confidence: 57%
“…PACAP and PAC1 receptor expression can be altered in several types of tumours such as thyroid papillary carcinoma or testis cancer (Bardosi et al 2016;Nakamura et al 2014). Previous findings have shown messenger RNA of PAC1, VPAC1 and VPAC2 in insulinoma cells (Borboni et al 1999). It is also known that PACAP inhibits pancreas islet mass expansion and pancreatic islet density, which is associated with islet neogenesis in type II diabetes (Inoue et al 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Maxadilan contains four cysteine residues, which form two disulfide bridges, one of which is located close to the N-terminus. Furthermore, it is known that the N-terminal residues of maxadilan are important for receptor binding 23, 29 . Therefore, it was thought likely that conjugation of DTPA to the N-terminus could influence the binding affinity.…”
Section: Discussionmentioning
confidence: 99%
“…As PAC1, VPAC1 and VPAC2 mRNAs were detected in a rat insulinoma cell line with PAC1 binding prevailing over that of VPAC1 and VPAC2 23 , the PAC1 receptor seemed to be a promising alternative for targeting insulinomas. The natural mammalian ligands at the PAC1 receptor are PACAP38 and the truncated form PACAP27.…”
Section: Introductionmentioning
confidence: 99%